SIMULATION-BASED ASSESSMENT KINERJA TERMAL PADA CONCENTRIC TUBE HEAT EXCHANGER - Kristiawan, Budi; Wijayanta, Agung Tri; Juwana, Wibawa Endra; Rachmanto, Rendy Adhi; Enoki, Koji; Prasojo, Arfi Singgih (Jurnal Rekayasa Mesin, 2023)
The double-pipe heat exchanger is one of the most popular heat exchanger devices. In this study, the concentric tube heat exchanger as the double pipe heat exchanger device was simulated with ANSYS code FLUENT. The simulation was done by based on the Reynolds number variation from 400010.000 using the method of co-current and counter flow. The hydrodynamic and thermal simulation results agree with the empirical correlation of the Pethukov and Dittus-Bolter equations, respectively. The friction factors of the water base fluid and nanofluid f TiO2/water f (0.1 vol.%) do not result in a significant difference in the turbulent flow regime for both co-current and counter flow. The thermal performance of TiO2/water (0.1% vol) nanofluid as indicated by the value of the heat transfer coefficient results in an increase of 6.9% for counter low flow and 6.0% for co-current flow. Meanwhile, the direction of fluid flow in the heat exchanger does not have a significant effect on its thermal performance.